Development of Standards for Metadata Documentation in Citizen Science Projects - Mantari Mincami, Lizet Doriela; Giron, Hilario Romero; Sanabria, Edith Mariela Quispe; Lago, Luis Alberto Poma; Vittes, Jose Francisco Via y Rada; Artica, Jessenia Vasquez; Ricapa, Linda Flor Villa (EAI Endorsed Transactions on Scalable Information Systems, 2024)
Introduction: Citizen science has generated large volumes of data contributed by citizens in the last decade. However, the lack of standardization in metadata threatens the interoperability and reuse of information.Objective: The objective was to develop a proposal for standards to document metadata in citizen science projects in order to improve interoperability and data reuse.Methods: A literature review was conducted that characterized the challenges in metadata documentation. Likewise, it analyzed previous experiences with standards such as Darwin Core and Dublin Core.Results: The review showed a high heterogeneity in the documentation, making interoperability difficult. The analyzes showed that standards facilitate the flow of information when they cover basic needs.Conclusions: It was concluded that standardizing metadata is essential to harness the potential of citizen science. The initial proposal, consisting of flexible norms focused on critical aspects, sought to establish bases for a collaborative debate considering the changing needs of this community.
Keywords: Citizen science; Metadata; Standards; Interoperability; Data reuse; Collaboration